Nanomaterials supported by polymers for tissue engineering applications: A review - Faezeh Habibzadeh; Seyed Mahdi Sadraei; Roghayeh Mansoori; Narendra Pal Singh Chauhan; Ghasem Sargazi (Heliyon, 2022)
In the biomedical sciences, particularly in wound healing, tissue engineering, and regenerative medicine, the development of natural-based biomaterials as a carrier has revealed a wide range of advantages. Tissue engineering is one of the therapeutic approaches used to replace damaged tissue. Polymers have received a lot of attention for their beneficial interactions with cells, but they have some drawbacks, such as poor mechanical properties. Due to their relatively large surface area, nanoparticles can cause significant changes in polymers and improve their mechanical properties. The nanoparticles incorporated into biomaterial scaffolds have been associated with positive effects on cell adhesion, viability, proliferation, and migration in the majority of studies. This review paper discusses recent applications of polymer-nanoparticle composites in the development of tissue engineering scaffolds, as well as the effects of these nanomaterials in the fields of cardiovascular, neural, bone, and skin tissue engineering.